THE SUPERVISION OF THE INTERNAL GOVERNMENT INTERNAL SUPERVISORY APPARATUS (APIP) ON THE ABUSE OF AUTHORITY IN GOVERNMENTAL POSITIONS IN JENEPONTO REGENCY - Mustaufiq, Mustaufiq; Sultan, Lomba; Ridwan, Muh. Saleh; Hasan, Hamzah (PT. Altin Riset Publishing, 2024)
The objective of this research was to examine the oversight conducted by the Government's Internal Control Apparatus (APIP) regarding the misuse of official authority within the Jeneponto District Government. This research employs a qualitative methodology with a sociological research approach. The informants include the Auditor of the Jeneponto Regency Government Internal Supervisory Apparatus, the Head of the Sub-Division of Discipline Development, Welfare, and Facilitation of the ASN Profession at the Jeneponto Regency Personnel and Human Resources Development Agency (BKPSDM), the Secretary and Acting Head of Treasury at the Jeneponto Regency Financial and Asset Management Agency, the Head of Budget at the Jeneponto Regency Financial and Asset Management Agency, and the Regent of Jeneponto. Data collection methods encompass observation, interviews, and documentation. Subsequently, the techniques for processing and analyzing data are executed through three distinct phases: data collection, data reduction, data presentation, and conclusion drawing. The outcomes indicate that: 1) The supervision by the Government Internal Supervisory Apparatus (APIP) over the abuse of authority in the Jeneponto Regency Government is not fully optimizing APIP's role in supervising, guiding, evaluating, and monitoring the duties and functions of regional apparatuses in the execution of bureaucratic activities. This is evidenced by the presence of several civil servants who have been implicated and directly involved in legal proceedings due to exceeding their official authority. 2) There is a shortage of qualified auditors, with the current number of personnel being insufficient relative to the number of civil servants requiring oversight across 11 sub-districts and 113 villages.